Industrial grade monoammonium phosphate crystal, preparation method thereof and iron phosphate crystal

By introducing desulfurization, defluorination and neutralization reaction steps in the wet phosphoric acid direct ammonia neutralization process, the problems of high energy consumption and pollution in the prior art were solved, and the production cost of industrial-grade monoammonium phosphate crystals was successfully reduced, while improving the quality and electrochemical performance of the product.

CN119750515AActive Publication Date: 2025-04-04HUBEI WANRUN NEW ENERGY TECH CO LTD

Patent Information

Application Number
CN202411907018.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-04
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

The prior art is difficult to significantly reduce the production cost of industrial-grade monoammonium phosphate crystals while maintaining high quality, and there are problems of high energy consumption and pollution.

Method used

The wet phosphoric acid direct ammonia neutralization process is adopted, and the desulfurization reaction is carried out by introducing a phosphate slurry, followed by adding a defluorination agent for the defluorination reaction, and the pH value is adjusted by ammonia-containing solution for neutralization. Finally, high-quality industrial-grade monoammonium phosphate crystals are obtained by concentration and cooling crystallization.

Benefits of technology

It achieves high-quality industrial-grade monoammonium phosphate crystals at low cost and low pollution, reduces impurity content, and improves the specific capacity and rate performance of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119750515A_ABST
    Figure CN119750515A_ABST
Patent Text Reader

Abstract

The invention provides an industrial-grade monoammonium phosphate crystal, a preparation method thereof and an iron phosphate crystal, and belongs to the field of battery materials, the industrial-grade monoammonium phosphate crystal is of a prism-shaped structure, the two ends of the prism are in a four-side conical shape, and the particle size of the prism is 500-700 microns; in percentage by mass, in the industrial grade monoammonium phosphate crystal, the content of P2O5 is greater than 61%, the content of N is greater than 11.5%, and the content of F ions is 50-150mg / kg. The wet-process phosphoric acid is used as a raw material, the phosphoric ore pulp, the defluorination agent and the ammonia-containing solution are sequentially introduced, desulfurization, defluorination and neutralization are performed respectively, and all reaction process parameters are strictly controlled, so that impurities are remarkably reduced; the prepared product is regular in particle morphology, uniform in particle size distribution and high in phosphorus and nitrogen content, and the lithium iron phosphate positive electrode material prepared from the precursor has good electrical properties; the preparation method has the advantages of simplicity in operation, easiness in reaction control, low cost and the like, and is suitable for large-scale industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of battery materials, and in particular to an industrial-grade monoammonium phosphate crystal and a preparation method thereof, an iron phosphate crystal, a lithium iron phosphate positive electrode material, a positive electrode sheet and a secondary battery. Background Art

[0002] Industrial grade monoammonium phosphate (MAP), also known as diammonium phosphate, is a white powdery or granular inorganic compound with a chemical formula of NH 4 H 2 PO 4 After dissolving, it dissociates into ammonium ions and phosphate ions, and has good chemical reactivity and thermal stability; it has a wide range of applications and can be used as fertilizers, flame retardants, food additives, feed additives, pharmaceutical buffers, battery materials, etc. Among them, in the application field of new energy batteries, iron phosphate is an important raw material for the preparation of lithium iron phosphate positive electrode materials, and industrial-grade monoammonium phosphate crystals are an important raw material for the preparation of iron phosphate. The process design of industrial-grade monoammonium phosphate crystals will affect the production cost and product quality of lithium iron phosphate positive electrode materials.

[0003] At present, the preparation methods of industrial-grade monoammonium phosphate crystals mainly include the following three process routes: thermal phosphoric acid ammonium neutralization process, wet phosphoric acid extraction and purification ammonia neutralization process, and wet phosphoric acid direct ammonia neutralization process. Among them, the monoammonium phosphate product produced by the thermal phosphoric acid ammonium neutralization process has high quality, but the process has high energy consumption, high production cost, and heavy pollution; the monoammonium phosphate product produced by the wet phosphoric acid extraction and purification ammonia neutralization process has medium quality, but the equipment and technology investment in the extraction and purification acid link are large, and the cost is high; the monoammonium phosphate product produced by the wet phosphoric acid direct ammonia neutralization process is lower in quality than the first two, but the investment is small and the production cost is low. It can be seen that it is difficult to significantly reduce the production cost under the premise of high quality of monoammonium phosphate products by using the above-mentioned existing process methods for industrial-grade monoammonium phosphate crystals.

[0004] Therefore, there is an urgent need to provide a new preparation method to obtain higher quality monoammonium phosphate crystals at a lower production cost. Summary of the invention

[0005] In view of the technical problems existing in the background technology, the present application provides an industrial-grade monoammonium phosphate crystal and a preparation method thereof, iron phosphate crystals, lithium iron phosphate positive electrode materials, positive electrode plates and secondary batteries, aiming to solve the problem of the lack of low-cost, low-pollution, high-quality monoammonium phosphate crystal preparation process in the prior art.

[0006] In a first aspect, the present invention provides an industrial-grade monoammonium phosphate crystal, wherein the industrial-grade monoammonium phosphate crystal has a prismatic structure, the two ends of the prism are four-sided pyramids, the particle size is 500-700 μm, and the aspect ratio is (2-4):1; in terms of mass percentage, in the industrial-grade monoammonium phosphate crystal, P 2 O 5 The content is greater than 61%, the N content is greater than 11.5%, and the F ion content is 50~150 mg / kg.

[0007] In the technical solution of the embodiment of the present application, the prepared industrial-grade monoammonium phosphate crystals have a prismatic structure, the two ends of the prism are four-sided pyramidal, the product particles have a regular morphology, and the particle size distribution is uniform, and wherein P 2 O 5 The N content is high, and the lithium iron phosphate positive electrode material prepared from the precursor has a high specific capacity and good rate performance.

[0008] In a second aspect, an embodiment of the present application provides a method for preparing industrial-grade monoammonium phosphate crystals, which is used to prepare the industrial-grade monoammonium phosphate crystals described in the first aspect, comprising the following steps: mixing wet-process phosphoric acid with phosphate slurry and performing a desulfurization reaction, followed by solid-liquid separation to obtain a first filter cake and a first filtrate; adding a defluorinating agent to the first filtrate to perform a defluorination reaction, followed by solid-liquid separation to obtain a second filter cake and a second filtrate; adding an ammonia solution to the second filtrate to adjust the pH to 4-5 and perform a neutralization reaction, followed by solid-liquid separation to obtain a third filter cake and a third filtrate; the third filtrate is concentrated, cooled and crystallized, and solid-liquid separated to obtain industrial-grade monoammonium phosphate crystals.

[0009] In the technical scheme of the embodiment of the present application, the preparation steps are designed based on the direct ammonia neutralization process of wet-process phosphoric acid, and wet-process phosphoric acid is used as a raw material. First, a phosphate slurry is introduced to remove the sulfur element in the wet-process phosphoric acid, and a defluorinating agent is introduced into the first filtrate after desulfurization to carry out a defluorination reaction, thereby effectively removing the sulfur and fluorine elements in the wet-process phosphoric acid; then, an ammonia-containing solution is introduced to neutralize the second filtrate after defluorination, and the pH value and reaction temperature of the neutralization reaction are adjusted to control the generation of monoammonium phosphate and inhibit its conversion to diammonium phosphate; subsequently, the third filtrate containing monoammonium phosphate is successively concentrated, cooled and crystallized, and solid-liquid separated. In the cooling and crystallization process, by controlling the cooling rate, stirring rate, crystallization time and other parameters, the impurity content in the industrial-grade monoammonium phosphate crystal is significantly reduced, the yield of the industrial-grade monoammonium phosphate crystal is increased, and the precipitation of high-quality industrial-grade monoammonium phosphate crystals is achieved, which is conducive to the subsequent preparation of high-quality iron phosphate crystals and lithium iron phosphate positive electrode materials. The preparation method of the present application has the advantages of simple operation, easy control of reaction conditions, low cost, etc., and is suitable for large-scale industrial production.

[0010] In some embodiments, in the step of mixing wet-process phosphoric acid with phosphate slurry and performing a desulfurization reaction, the desulfurization reaction temperature is 80-90° C., and the desulfurization reaction time is 3-4 h; 2 O 5 The mass percentage is greater than 20%, and the Ca content in phosphate slurry is 2+ SO in wet-process phosphoric acid 4 2- The molar ratio is (0.8~1.0):1.

[0011] In this embodiment, phosphate rock powder is added to wet-process phosphoric acid to carry out desulfurization reaction and generate gypsum, and the phosphate rock powder is used to remove the residual sulfate in the wet-process phosphoric acid; by adjusting the ratio of wet-process phosphoric acid to phosphate slurry (especially Ca in the phosphate slurry), 2+ SO in wet-process phosphoric acid 4 2- ratio), and control the desulfurization reaction temperature and time to improve the desulfurization efficiency while reducing energy consumption and production costs. Specifically, under the condition that the dosage of other components is the same, if the dosage of phosphate slurry is too much, after the sulfate ions remaining in the wet sulfuric acid are completely reacted, more cationic impurities will be introduced, which will reduce the subsequent phosphorus yield; if the dosage of phosphate slurry is insufficient, it cannot completely react with the sulfate ions remaining in the wet sulfuric acid, resulting in insufficient desulfurization. For the control of the desulfurization reaction temperature, if the desulfurization reaction temperature is too high, it will lead to an increase in side reactions, affecting the desulfurization efficiency, and may also cause corrosion to equipment materials and increase energy consumption; if the desulfurization reaction temperature is low, the desulfurization efficiency will be reduced. For the control of the desulfurization reaction time, if the desulfurization reaction time is too long, although the desulfurization efficiency can be improved to a certain extent, the excessive reaction time will also lead to a decrease in the stability of the reaction system and increase production costs; if the desulfurization reaction time is insufficient, the desulfurization efficiency will be reduced.

[0012] In some embodiments, in the step of adding a defluorinating agent to the first filtrate for defluorinating reaction, the defluorinating reaction temperature is 50-80°C, and the defluorinating reaction time is 2-4 h; wherein the defluorinating agent includes at least one of sodium hydroxide, sodium carbonate, sodium bicarbonate, potassium hydroxide, potassium carbonate, and potassium bicarbonate, and the cations in the defluorinating agent are compatible with the F in the first filtrate. - The molar ratio is (1.2~1.4):3.

[0013] In this embodiment, a defluorinating agent is added to the first filtrate after desulfurization to carry out a defluorination reaction. The defluorinating agent can be a soluble sodium salt or potassium salt and does not contain sulfur element to avoid reintroduction of sulfur element after desulfurization. Sodium fluorosilicate or potassium fluorosilicate slightly soluble in water is generated during the defluorination reaction, and the fluorine element is removed after solid-liquid separation. By adjusting the ratio of the defluorinating agent to the first filtrate (especially the Na in the defluorinating agent), the defluorinating agent can be used to remove the fluorine element. + and / or K + With the first filtrate F -ratio), and control the defluorination reaction temperature and time to improve the defluorination efficiency while reducing energy consumption and production costs. Specifically, under the condition that the dosage of other components is the same, if the dosage of the defluorinating agent is too much, although the defluorination efficiency can be improved, too much defluorinating agent not only increases the cost of raw materials, but its excessive cationic part will combine with phosphate and form insoluble phosphate fluoride, resulting in a decrease in phosphorus yield in the subsequent preparation process; if the dosage of the defluorinating agent is insufficient, it cannot completely react with the fluorosilicate remaining in the first filtrate after desulfurization, resulting in insufficient defluorination. For the control of the defluorination reaction temperature, if the defluorination reaction temperature is too high, although the defluorination efficiency can be improved to a certain extent, the defluorination rate will not be significantly improved after exceeding a certain reaction temperature, but it will greatly increase energy consumption; if the defluorination reaction temperature is low, the defluorination efficiency will be reduced. Regarding the control of defluorination reaction time, if the defluorination reaction time is too long, although the defluorination efficiency can be improved to a certain extent, the improvement effect of the defluorination rate is not obvious after exceeding a certain reaction time, but it will greatly increase the production cost; if the defluorination reaction time is insufficient, the defluorination efficiency will be reduced.

[0014] In some embodiments, in the neutralization reaction step, an ammonia-containing solution is added to adjust the pH to 4-5 and perform a neutralization reaction, the neutralization reaction temperature is 70-90°C, and the neutralization reaction time is 1.5-3 h; wherein the ammonia-containing solution includes at least one of liquid ammonia and ammonia water.

[0015] In this embodiment, an alkaline ammonia solution is added to the second filtrate after desulfurization and defluorination to carry out a neutralization reaction. The pH value of the neutralization reaction is adjusted by the ammonia solution, and the temperature and time of the neutralization reaction are controlled at the same time, so that phosphoric acid and ammonium ions fully react to form monoammonium phosphate, and impurities such as iron, aluminum, calcium, and magnesium are removed at the same time. Specifically, with respect to the control of the pH value of the neutralization reaction, as the pH value increases, the crystallization efficiency of monoammonium phosphate tends to first increase and then decrease. If the pH value is too high (i.e., too much alkaline ammonia solution is added), the crystallization efficiency of monoammonium phosphate will be significantly reduced; if the pH value is too low (i.e., insufficient alkaline ammonia solution is added), not only will impurities such as iron, aluminum, calcium, and magnesium be difficult to remove, but phosphoric acid will also be excessive and unable to fully react to form monoammonium phosphate. With respect to the control of the neutralization reaction temperature, the temperature will have an impact on NH 4 OH and HPO 4 2- If the temperature is too high, the generation of monoammonium phosphate will be accelerated. At the same time, the solubility of monoammonium phosphate increases sharply with the increase of temperature, and the amount of ammonia released increases with the temperature, which affects the stability of the generated monoammonium phosphate and is not conducive to subsequent crystallization. If the temperature is too low, the generation of monoammonium phosphate is slow, and impurities such as iron, aluminum, calcium, and magnesium are difficult to fully remove. For the control of the neutralization reaction time, the impurity removal efficiency gradually increases with the extension of the reaction time, and gradually slows down after reaching a certain level. Therefore, appropriately extending the reaction time is helpful to improve the impurity removal efficiency.

[0016] In some embodiments, the specific conditions for cooling crystallization include: cooling rate of 0.2-0.6°C / min, stirring rate of 150-300 rpm, crystallization time of 4-7 h, and solid-liquid ratio of 30-60% after cooling.

[0017] In this embodiment, the third filtrate obtained after the neutralization reaction is sequentially concentrated, cooled and crystallized, and solid-liquid separated. In the cooling and crystallization process, the cooling rate, stirring rate, crystallization time, and solid-liquid ratio after cooling are all key factors affecting the growth of monoammonium phosphate crystals and product quality. For the control of the cooling rate, stirring rate, and crystallization time, if the cooling rate is too slow, or the stirring rate is low, or the crystallization time is too long, although it is conducive to the growth of complete crystals, the efficiency is low and it is not conducive to industrial production; if the cooling rate is too fast, or the stirring rate is fast, or the crystallization time is too short, the crystal growth is incomplete and the grains are small, and the quality is low. For the control of the solid-liquid ratio after cooling, if the solid-liquid ratio is too high, the crystal growth rate is slow and the crystal particle size increases; if the solid-liquid ratio is too low, the crystal growth rate is fast and the crystal particle size decreases, so it is necessary to control the solid-liquid ratio after cooling to be in an appropriate range so that the obtained crystals are not too large or too small.

[0018] In some embodiments, after cooling, crystallization and solid-liquid separation, the obtained solid phase is industrial-grade monoammonium phosphate crystals, and the liquid phase is refluxed into wet-process phosphoric acid and undergoes desulfurization reaction again with the phosphate slurry.

[0019] In this embodiment, after cooling, crystallization and solid-liquid separation, the obtained liquid phase is reused as mother liquor and subjected to desulfurization reaction again with wet-process phosphoric acid and phosphate slurry, so that the remaining phosphorus therein can be fully recovered, thereby improving the utilization rate of phosphorus.

[0020] In some embodiments, the first filter cake is recycled to the extraction process section in the wet phosphoric acid preparation process for preparing wet phosphoric acid; the second filter cake is dried and recycled as a fluorosilicate product; and the third filter cake is dried and recycled as a slow-release nitrogen and phosphorus fertilizer.

[0021] In this embodiment, the first filter cake obtained after the desulfurization reaction mainly contains phosphate, sulfate, etc., which are recycled to the extraction process section and used to prepare wet-process phosphoric acid again, which can effectively improve the utilization rate of phosphorus; the second filter cake obtained after the defluorination reaction mainly contains sodium fluorosilicate or potassium fluorosilicate, etc., which can be recovered in the form of fluorosilicate products; the third filter cake obtained after the neutralization reaction is mainly a complex salt containing ammonia and phosphate, which can be recycled as a slow-release nitrogen and phosphorus fertilizer after drying. Therefore, the first filter cake, the second filter cake and the third filter cake can be recycled respectively, which effectively avoids the generation of waste in the preparation process and makes the process more green and environmentally friendly.

[0022] In a third aspect, an embodiment of the present application provides an iron phosphate crystal, which is obtained by a mixed reaction of an iron salt solution, an oxidant, and the industrial-grade monoammonium phosphate crystals in the first aspect; wherein the iron salt in the iron salt solution includes at least one of ferrous sulfate, ferrous chloride, ferric sulfate, and ferric chloride, and the oxidant includes hydrogen peroxide.

[0023] In the technical solution of the embodiment of the present application, the iron phosphate crystal product prepared from the aforementioned industrial-grade monoammonium phosphate crystals has regular particle morphology, uniform particle size distribution and excellent performance, and the lithium iron phosphate positive electrode material prepared from the iron phosphate crystals has a higher specific capacity and better rate performance.

[0024] In a fourth aspect, an embodiment of the present application provides a lithium iron manganese phosphate positive electrode material, which is obtained by a mixed reaction of the iron phosphate crystals provided in the third aspect of the present application and a lithium source.

[0025] The lithium iron manganese phosphate positive electrode material of the present application is prepared from the aforementioned iron phosphate crystals, and thus has the advantages of high specific capacity and good rate performance.

[0026] In a fifth aspect, an embodiment of the present application provides a positive electrode plate, comprising the lithium iron manganese phosphate positive electrode material provided in the fourth aspect of the present application.

[0027] The positive electrode plate of the present application includes the aforementioned lithium iron manganese phosphate positive electrode material, and thus has the advantages of high specific capacity and good rate performance.

[0028] In a sixth aspect, an embodiment of the present application provides a secondary battery, comprising the positive electrode plate provided in the fifth aspect of the present application.

[0029] The secondary battery of the present application includes the aforementioned positive electrode plate, and thus has the advantages of high specific capacity and good rate performance.

[0030] Compared with the prior art, the beneficial effects of this application include: The present application uses wet-process phosphoric acid as a raw material, sequentially introduces phosphate slurry, a defluorinating agent and an ammonia-containing solution, respectively performs desulfurization reaction, defluorination reaction and neutralization reaction, and strictly controls the process parameters of the desulfurization reaction, defluorination reaction and neutralization reaction, so that impurities such as sulfur, fluorine, iron, aluminum, calcium and magnesium are significantly reduced; the prepared industrial-grade monoammonium phosphate crystals have a prismatic structure, the product particles have a regular morphology, a uniform particle size distribution, and a high content of phosphorus and nitrogen, and the lithium iron phosphate positive electrode material prepared from the precursor has a high specific capacity and good rate performance; the preparation method of the present application has the advantages of simple operation, easy control of reaction conditions, low cost and the like, and is suitable for large-scale industrial production.

[0031] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0033] Figure 1 A process flow chart of an embodiment of a method for preparing industrial-grade monoammonium phosphate crystals provided in an example of the present application; Figure 2 These are SEM images of industrial-grade monoammonium phosphate crystals obtained in Examples 1 to 5 of the present application: a to e are industrial-grade monoammonium phosphate crystals obtained in Examples 1 to 5, respectively. DETAILED DESCRIPTION

[0034] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0035] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0036] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0037] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0038] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0039] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).

[0040] The direct ammonia neutralization process of wet-process phosphoric acid is a method for preparing monoammonium phosphate by ammonia neutralization reaction of wet-process phosphoric acid. In the prior art, one or more ammonia neutralizations are usually used, followed by concentration, crystallization and drying to prepare monoammonium phosphate crystals. Although this process has low investment and low production cost, the prepared monoammonium phosphate crystals are usually of low quality, and it is difficult to obtain high-quality crystals with regular microscopic morphology and uniform particle size distribution. The reason is that the raw material wet-process phosphoric acid contains F, SO 4 2- , Fe, Al, Ca, Mg and other impurities, which will exist in the form of phosphate complex salts during the ammonia neutralization process. However, it is difficult to fully remove the above impurity elements during the ammonia neutralization process in the existing process, resulting in residual impurities affecting the preparation of monoammonium phosphate crystals. For example, in the existing ammonia neutralization process, impurity F - After ammonia is neutralized, there will still be a large amount of residue, which will reduce the phosphorus yield in the preparation process of monoammonium phosphate. - The presence of F may accelerate the aging and corrosion of production equipment, and - The emission of impurities SO 4 2- The presence of will reduce the width of the metastable zone, which will not only cause the morphology of the prepared monoammonium phosphate crystals to change due to dislocation growth, but also affect the particle size and uniformity during the crystallization process.

[0041] The other two existing processes for preparing monoammonium phosphate crystals also have shortcomings. The monoammonium phosphate produced by the thermal phosphoric acid ammonium neutralization process has high quality, but the process has high energy consumption, high production cost and heavy pollution. The monoammonium phosphate produced by the wet phosphoric acid extraction and purification ammonia neutralization process has medium quality, but the equipment and technology investment in the extraction and purification of acid is large and the cost is high.

[0042] In order to solve the technical problem of lack of low-cost, low-pollution, high-quality monoammonium phosphate crystal preparation process in the existing process for preparing industrial-grade monoammonium phosphate crystals, the present application provides an industrial-grade monoammonium phosphate crystal and its preparation method, iron phosphate crystal, lithium iron phosphate positive electrode material, positive electrode plate and secondary battery. The present application uses wet-process phosphoric acid as raw material, introduces phosphate slurry, defluorination agent and ammonia solution in sequence, and respectively carries out desulfurization reaction, defluorination reaction and neutralization reaction, and strictly controls the process parameters of desulfurization reaction, defluorination reaction and neutralization reaction, so that impurities such as sulfur, fluorine, iron, aluminum, calcium and magnesium are significantly reduced; the prepared industrial-grade monoammonium phosphate crystal has a prismatic structure, the product particle morphology is regular, the particle size distribution is uniform, and the phosphorus and nitrogen content are high, and the lithium iron phosphate positive electrode material prepared from the precursor has a high specific capacity and good rate performance.

[0043] In a first aspect, the present invention provides an industrial-grade monoammonium phosphate crystal, wherein the industrial-grade monoammonium phosphate crystal has a prismatic structure, the two ends of the prism are four-sided pyramidal, the particle size is 500-700 μm, and the aspect ratio is (2-4):1; in terms of mass percentage, the industrial-grade monoammonium phosphate crystal has a P 2 O 5 The content is greater than 61%, the N content is greater than 11.5%, and the F ion content is 50~150mg / kg.

[0044] In the technical solution of the embodiment of the present application, the industrial-grade monoammonium phosphate crystals prepared are prismatic in structure, with four-sided pyramids at both ends of the prism, and have a specific microscopic morphology and aspect ratio range. During the preparation process, the impurity content will affect the microscopic morphology and aspect ratio, and the impurity content needs to be strictly controlled to obtain the industrial-grade monoammonium phosphate crystals of the above morphology. For example, SO 4 2- When the content is too high, the crystals will grow out of place, forming X-shaped crystals, which will significantly change the microscopic morphology; the presence of impurities such as iron and aluminum ions will inhibit the growth of monoammonium phosphate crystals. At the same time, when the impurities are too much, the prismatic structure of the crystals will become longer, the aspect ratio will become larger, and the prepared monoammonium phosphate crystals will be difficult to filter.

[0045] See also Figure 1 In a second aspect, the present application provides a method for preparing industrial-grade monoammonium phosphate crystals, comprising the following steps: S1, mixing wet-process phosphoric acid with phosphate slurry and performing a desulfurization reaction, followed by solid-liquid separation to obtain a first filter cake and a first filtrate; S2, adding a defluorinating agent to the first filtrate to carry out a defluorinating reaction, followed by solid-liquid separation to obtain a second filter cake and a second filtrate; S3, adding an ammonia solution to the second filtrate to adjust the pH to 4-5 and perform a neutralization reaction, followed by solid-liquid separation to obtain a third filter cake and a third filtrate; S4. The third filtrate is concentrated, cooled and crystallized, and solid-liquid separated to obtain industrial-grade monoammonium phosphate crystals.

[0046] In the technical scheme of the embodiment of the present application, the preparation steps are designed based on the direct ammonia neutralization process of wet-process phosphoric acid, and wet-process phosphoric acid is used as raw material to carry out desulfurization reaction, defluorination reaction and neutralization reaction in sequence. First, phosphate slurry is introduced to remove sulfur elements in wet-process phosphoric acid, and a defluorinating agent is introduced into the first filtrate after desulfurization to carry out defluorination reaction, thereby effectively removing sulfur and fluorine elements in wet-process phosphoric acid; then, an ammonia-containing solution is introduced to neutralize the second filtrate after defluorination, and the pH value and reaction temperature of the neutralization reaction are adjusted to control the generation of monoammonium phosphate and inhibit its conversion to diammonium phosphate; subsequently, the third filtrate containing monoammonium phosphate is concentrated, cooled and crystallized, and solid-liquid separated in sequence. In the cooling and crystallization process, the impurity content in the industrial-grade monoammonium phosphate crystal is significantly reduced by controlling the cooling rate, stirring rate, crystallization time and other parameters, and the yield of industrial-grade monoammonium phosphate crystals is improved, and the precipitation of high-quality industrial-grade monoammonium phosphate crystals is achieved, which is conducive to the subsequent preparation of high-quality iron phosphate crystals and lithium iron phosphate positive electrode materials.

[0047] Further, in some embodiments, in step S1, the desulfurization reaction temperature is 80-90°C, and the desulfurization reaction time is 3-4 h; specifically, the desulfurization reaction temperature includes but is not limited to any point value among 80°C, 83°C, 85°C, 88°C, and 90°C, or any range value between the two, and the desulfurization reaction time includes but is not limited to any point value among 3 h, 3.5 h, and 4 h, or any range value between the two. 2 O 5 The mass percentage is greater than 20%, and the Ca content in phosphate slurry is 2+ SO in wet-process phosphoric acid 4 2- The molar ratio of Ca in phosphate slurry is (0.8~1.0):1; specifically, 2+ SO in wet-process phosphoric acid 4 2- The molar ratio includes but is not limited to any point value among 0.8:1, 0.9:1, 1:1 or any range value between the two. In this embodiment, the solid-liquid separation is performed by filter pressing. In other embodiments, the specific solid-liquid separation method or device used can be adaptively adjusted according to actual needs, which is not limited here.

[0048] In the technical solution of the embodiment of the present application, phosphate rock powder is added to wet-process phosphoric acid to carry out a desulfurization reaction and generate gypsum, and the phosphate rock powder is used to remove the residual sulfate in the wet-process phosphoric acid. After the sulfate is fully removed, its effect on the microscopic morphology of the crystal can be significantly weakened, so that it can be crystallized in a prismatic structure. Specifically, by adjusting the ratio of wet-process phosphoric acid to phosphate slurry (especially Ca in the phosphate slurry),2+ SO in wet-process phosphoric acid 4 2- The ratio of MAP to PH value is controlled by adjusting the reaction temperature and time of desulfurization to improve desulfurization efficiency while reducing energy consumption and production costs. Specifically, under the condition that the dosage of other components is the same, if the dosage of phosphate slurry is too much, more cationic impurities will be introduced after the residual sulfate in wet sulfuric acid is completely reacted, which will reduce the subsequent phosphorus yield; at the same time, it is also found through experiments that when the sulfate content is too low, after cooling and crystallization, the proportion of fine MAP crystals (average particle size is far less than 500 μm) increases, thereby reducing the number of MAP crystals with regular and uniform particle size (particle size 500~700 μm) obtained in a single preparation process. μm), that is, it is difficult to obtain an ideal MAP crystal particle size distribution state. Although fine MAP crystals can be used as mother liquor and recycled to the next cycle of preparation process, the excessive recycling of fine MAP crystals will undoubtedly reduce the preparation amount of MAP crystals with regular and uniform particle size in a single time; if the amount of phosphate slurry is insufficient, it cannot completely react with the sulfate ions remaining in the wet sulfuric acid, resulting in insufficient desulfurization; it can be seen that it is necessary to strictly control the sulfur content of the prepared MAP crystals by controlling the amount of phosphate rock powder to achieve a higher phosphorus yield, while reducing the content of fine crystals in the preparation process of MAP crystals, and obtaining MAP crystals with ideal particle size distribution and less impurity content. For the control of the desulfurization reaction temperature, if the desulfurization reaction temperature is too high, it will lead to an increase in side reactions, affecting the desulfurization efficiency, and may also cause corrosion to equipment materials and increase energy consumption; if the desulfurization reaction temperature is too low, it will reduce the desulfurization efficiency. Regarding the control of desulfurization reaction time, if the desulfurization reaction time is too long, although it can improve the desulfurization efficiency to a certain extent, too long a reaction time will also lead to a decrease in the stability of the reaction system and increase production costs; if the desulfurization reaction time is insufficient, the desulfurization efficiency will be reduced. Therefore, it is necessary to control the desulfurization reaction temperature, desulfurization reaction time and Ca content in the phosphate slurry. 2+ SO in wet-process phosphoric acid 4 2- The best desulfurization effect can only be achieved when the molar ratio is controlled within the above appropriate range.

[0049] In some embodiments, in the step of adding a defluorinating agent to the first filtrate for defluorinating reaction, the defluorinating reaction temperature is 50-80°C, and the defluorinating reaction time is 2-4 h; specifically, the defluorinating reaction temperature includes but is not limited to any point value among 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C or any range value between two of them, and the defluorinating reaction time includes but is not limited to any point value among 2 h, 2.5 h, 3 h, 3.5 h, 4 h or any range value between two of them. Wherein, the defluorinating agent includes at least one of sodium hydroxide, sodium carbonate, sodium bicarbonate, potassium hydroxide, potassium carbonate, and potassium bicarbonate, and the cations in the defluorinating agent are compatible with the F in the first filtrate. -The molar ratio of the cation in the defluorinating agent to the F in the first filtrate is (1.2~1.4):3; - The molar ratio includes but is not limited to any point value among 1.2:3, 1.3:3, 1.4:3 or any range value between the two. In this embodiment, the solid-liquid separation is performed by filter pressing. In other embodiments, the specific solid-liquid separation method or device used can be adaptively adjusted according to actual needs, which is not limited here.

[0050] In the technical solution of the embodiment of the present application, a defluorinating agent is added to the first filtrate after desulfurization to carry out a defluorination reaction. The defluorinating agent can be a soluble sodium salt or potassium salt and does not contain sulfur to avoid the reintroduction of sulfur after desulfurization. Sodium fluorosilicate or potassium fluorosilicate slightly soluble in water is generated during the defluorination reaction. The fluorine element is removed after solid-liquid separation. After being fully removed, the fluorine element can significantly reduce the defluorination pressure of the subsequent neutralization reaction process, reduce the residual fluoride ions, and improve the phosphorus yield of the subsequent preparation process. Specifically, by adjusting the ratio of the defluorinating agent to the first filtrate (especially the Na in the defluorinating agent), the defluorinating agent can be used to remove the fluorine element. + and / or K + With the first filtrate F - ratio), and control the defluorination reaction temperature and time, improve the defluorination efficiency, and reduce energy consumption and production costs. Specifically, under the condition that the dosage of other components is the same, if the dosage of the defluorinating agent is too much, although the defluorination efficiency can be improved, too much defluorinating agent not only increases the cost of raw materials, but its excessive cationic part will combine with phosphate to form insoluble phosphate fluoride, resulting in a decrease in phosphorus yield in the subsequent preparation process. At the same time, it is also found through experiments that a small amount of fluoride ions can promote MAP crystallization. When too much defluorinating agent is introduced to reduce fluoride ions sharply, too few fluoride ions are difficult to promote MAP crystallization, so that the obtained grains are small; if the dosage of the defluorinating agent is insufficient, it cannot completely react with the fluorosilicate remaining in the first filtrate after desulfurization, so that the defluorination is insufficient; it can be seen that it is necessary to strictly control the fluorine content of the prepared MAP crystals by controlling the dosage of the defluorinating agent, so as to achieve the preparation of MAP crystals to obtain a good phosphorus yield and grain size at the same time. Regarding the control of the defluorination reaction temperature, if the defluorination reaction temperature is too high, although the defluorination efficiency can be improved to a certain extent, the defluorination rate will not be significantly improved after exceeding a certain reaction temperature, and the energy consumption will be greatly increased; if the defluorination reaction temperature is too low, the defluorination efficiency will be reduced. Regarding the control of the defluorination reaction time, if the defluorination reaction time is too long, although the defluorination efficiency can be improved to a certain extent, the defluorination rate will not be significantly improved after exceeding a certain reaction time, and the production cost will be greatly increased; if the defluorination reaction time is insufficient, the defluorination efficiency will be reduced. Therefore, it is necessary to adjust the defluorination reaction temperature, defluorination reaction time, and the cations in the defluorination agent and the F in the first filtrate. - The best defluorination effect can be obtained only when the molar ratio of is controlled within the above appropriate range.

[0051] In some embodiments, in the step of neutralization reaction, an ammonia-containing solution is added to adjust the pH to 4-5 and a neutralization reaction is carried out, the neutralization reaction temperature is 70-90°C, and the neutralization reaction time is 1.5-3 h; specifically, the pH value includes but is not limited to any point value of 4.0, 4.2, 4.4, 4.6, 4.8, 5.0 or any range value between two, the neutralization reaction temperature includes but is not limited to any point value of 70°C, 75°C, 80°C, 85°C, 90°C or any range value between two, and the neutralization reaction time includes but is not limited to any point value of 1.5h, 2h, 2.5h, 3h or any range value between two. Among them, the ammonia-containing solution includes at least one of liquid ammonia and ammonia water. In this embodiment, a filter press is used for solid-liquid separation. In other embodiments, the specific solid-liquid separation method or device used can be adaptively adjusted according to actual needs, and is not limited here.

[0052] In the technical solution of the embodiment of the present application, an alkaline ammonia solution is added to the second filtrate after desulfurization and defluorination for neutralization reaction. The pH value of the neutralization reaction is adjusted by the ammonia solution, and the temperature and time of the neutralization reaction are controlled at the same time, so that phosphoric acid and ammonium ions fully react to form monoammonium phosphate crystals, and impurities such as iron, aluminum, calcium, and magnesium are removed at the same time. Specifically, with respect to the control of the pH value of the neutralization reaction, as the pH value increases, the crystallization efficiency of monoammonium phosphate tends to first increase and then decrease. If the pH value is too high (i.e., too much alkaline ammonia solution is added), a viscous precipitate will be formed, making it difficult for monoammonium phosphate to form, and its crystallization efficiency will be significantly reduced; if the pH value is too low (i.e., insufficient alkaline ammonia solution is added), not only will impurities such as iron, aluminum, calcium, and magnesium be difficult to remove, but phosphoric acid will also be excessive and unable to fully react to form monoammonium phosphate. With respect to the control of the neutralization reaction temperature, the temperature will have an impact on NH 4 OH and HPO 4 2- The ionization equilibrium of monoammonium phosphate will be affected. If the temperature is too high, the formation of monoammonium phosphate will be accelerated. At the same time, the solubility of monoammonium phosphate will increase sharply with the increase of temperature, and the amount of ammonia escape will increase with the temperature being too high, thereby affecting the stability of the generated monoammonium phosphate, which is not conducive to subsequent crystallization; if the temperature is too low, the generation of monoammonium phosphate will be slow, and impurities such as iron, aluminum, calcium, and magnesium are difficult to fully remove. For the control of the neutralization reaction time, the impurity removal efficiency gradually increases with the extension of the reaction time, and gradually slows down after reaching a certain level. Appropriately extending the reaction time will help improve the impurity removal efficiency. Therefore, it is necessary to control the pH value, neutralization reaction temperature, and neutralization reaction time within the above-mentioned appropriate range to obtain the best neutralization reaction effect.

[0053] In some embodiments, the specific conditions for cooling crystallization include: a cooling rate of 0.2~0.6℃ / min, a stirring rate of 150~300 rpm, a crystallization time of 4~7 h, and a solid-liquid ratio of 30~60% after cooling; specifically, the cooling rate includes but is not limited to any point value of 0.2℃ / min, 0.4℃ / min, 0.6℃ / min or a range value between any two of them, the stirring rate includes but is not limited to any point value of 150 rpm, 200 rpm, 250 rpm, 300 rpm or a range value between any two of them, the crystallization time includes but is not limited to any point value of 4 h, 5 h, 6 h, 7 h or a range value between any two of them, and the solid-liquid ratio after cooling includes but is not limited to any point value of 30%, 40%, 50%, 60% or a range value between any two of them.

[0054] In the technical scheme of the embodiment of the present application, the third filtrate obtained after the neutralization reaction is sequentially concentrated, cooled and crystallized, and solid-liquid separated. In the cooling and crystallization process, the cooling rate, stirring rate, crystallization time, and solid-liquid ratio after cooling are all key factors affecting the growth of monoammonium phosphate crystals and product quality. For the control of the cooling rate, stirring rate, and crystallization time, if the cooling rate is too slow or the crystallization time is too long, although it is conducive to the growth of complete crystals, the efficiency is low and it is not conducive to industrial production; if the cooling rate is too fast or the crystallization time is too short, the crystal growth is incomplete and the grains are small, and the quality is low. For the control of the solid-liquid ratio after cooling, if the solid-liquid ratio is too high, the crystal growth rate is slow and the crystal particle size increases; if the solid-liquid ratio is too low, the crystal growth rate is fast and the crystal particle size decreases, so it is necessary to control the solid-liquid ratio after cooling to be in an appropriate range so that the obtained crystals are not too large or too small. If the stirring speed is too slow, the solid-phase mass transfer rate and solute growth rate are low, and the average particle size of the formed crystals is small; when a certain speed of 180rpm is reached, the solid-phase mass transfer rate and solute growth rate increase rapidly, and the average particle size of the crystals increases rapidly; if the stirring speed is too fast, the impact strength between the crystals and the stirring paddle will further increase, and at this time, the secondary nucleation phenomenon between crystals and the probability of crystal breakage, and the violent collision between crystals and stirring paddles will also greatly increase, ultimately resulting in a decrease in the average particle size of the product. Therefore, it is necessary to control the cooling rate, stirring rate, crystallization time, and solid-liquid ratio after cooling within the above appropriate range to obtain the best crystallization effect.

[0055] In some embodiments, after cooling, crystallization and solid-liquid separation, the obtained solid phase is industrial-grade monoammonium phosphate crystals, and the liquid phase is refluxed into wet-process phosphoric acid and desulfurized again with the phosphate slurry. In this embodiment, a filter press is used for solid-liquid separation. In other embodiments, the specific solid-liquid separation method or device used can be adaptively adjusted according to actual needs, and is not limited here.

[0056] In the technical solution of the embodiment of the present application, after cooling, crystallization and solid-liquid separation, the obtained liquid phase is reused as the mother liquor, and desulfurization reaction is carried out again with wet-process phosphoric acid and phosphate slurry, so that the remaining phosphorus therein is fully recovered, thereby improving the utilization rate of phosphorus; at the same time, since the impurities are mainly separated by the third filter cake after the neutralization reaction, the impurity content in the third filtrate is extremely small, so that when the liquid phase after cooling, crystallization and solid-liquid separation is reused as the mother liquor, there will not be many impurities enriched with the reflux, so that it will not affect the crystallization of monoammonium phosphate after multiple cycle reactions as the mother liquor, thereby realizing the continuous industrial production of high-quality industrial-grade monoammonium phosphate crystals.

[0057] In some embodiments, the first filter cake is recycled to the extraction process section in the wet phosphoric acid preparation process for preparing wet phosphoric acid; the second filter cake is dried and recycled as a fluorosilicate product; and the third filter cake is dried and recycled as a slow-release nitrogen and phosphorus fertilizer.

[0058] In the technical scheme of the embodiment of the present application, the first filter cake obtained after the desulfurization reaction mainly contains phosphate, sulfate, etc., which is recycled to the extraction process section and wet-process phosphoric acid is prepared again. The prepared wet-process phosphoric acid can be used as a raw material to perform the above preparation steps again, thereby effectively improving the utilization rate of phosphorus; in other embodiments, the first filter cake can also be recycled to other process sections for preparing wet-process phosphoric acid to achieve a similar reuse effect as above, which is not limited here. The second filter cake obtained after the defluorination reaction mainly contains sodium fluorosilicate or potassium fluorosilicate, etc., which can be recovered in the form of fluorosilicate products. The recovered fluorosilicates can be used as building materials, metal electroplating materials, preservatives, pesticides, plastic fillers, etc., and its specific application method can be adaptively selected according to actual needs, which is not limited here. The third filter cake obtained after the neutralization reaction is mainly a complex salt containing ammonia and phosphate, which can be recycled as a slow-release nitrogen and phosphorus fertilizer after drying. The third filter cake can also be adapted and deployed according to actual needs, and a slow-release nitrogen and phosphorus fertilizer that meets the needs has been obtained, which is not limited here. Thus, the first filter cake, the second filter cake and the third filter cake can be reused respectively, so that all products obtained in the aforementioned process steps can be utilized, effectively avoiding the generation of waste in the preparation process and making the process more green and environmentally friendly.

[0059] In a third aspect, an embodiment of the present application provides an iron phosphate crystal, which is obtained by a mixed reaction of an iron salt solution, an oxidant, and the industrial-grade monoammonium phosphate crystals in the first aspect; wherein the iron salt in the iron salt solution includes at least one of ferrous sulfate, ferrous chloride, ferric sulfate, and ferric chloride, and the oxidant includes hydrogen peroxide.

[0060] In the technical solution of the embodiment of the present application, the iron phosphate crystal product prepared from the aforementioned industrial-grade monoammonium phosphate crystal has a regular particle morphology, uniform particle size distribution and excellent performance, and the lithium iron phosphate positive electrode material prepared from the iron phosphate crystal has a high specific capacity and good rate performance. In other embodiments, other conventional raw materials can be selected as iron salts or oxidants for preparing iron phosphate crystals according to actual needs, which are not limited here.

[0061] In a fourth aspect, an embodiment of the present application provides a lithium iron manganese phosphate positive electrode material, which is obtained by a mixed reaction of the iron phosphate crystals provided in the third aspect of the present application and a lithium source.

[0062] In the technical solution of the embodiment of the present application, the lithium iron phosphate manganese positive electrode material is prepared by uniformly mixing the industrial-grade iron phosphate crystals provided in the third aspect of the present application with a lithium source and then adopting a high-temperature solid-phase method; or by uniformly mixing the aforementioned industrial-grade iron phosphate crystals, a lithium source, and a carbon source and then adopting a high-temperature solid-phase method. Among them, the molar ratio of iron phosphate crystals to lithium source is 1: (1~1.03), the molar ratio of iron phosphate crystals to carbon source is 1: (0.01~0.2), the lithium source includes at least one of lithium carbonate and lithium hydroxide, and the carbon source includes at least one of glucose, sucrose, fructose, cellulose, starch, citric acid, polyacrylic acid, polyethylene glycol and dopamine. The high-temperature solid phase method is high-temperature gradient calcination. During the high-temperature gradient calcination, the calcination temperature of the first stage is 350~450℃, and the insulation time of the first stage is 2~6h; the calcination temperature of the second stage is 760~790℃, and the insulation time of the second stage is 2~6h; the calcination temperature of the third stage is 600~700℃, and the insulation time of the third stage is 2~6h. The iron manganese phosphate lithium positive electrode material of the present application is prepared from the above-mentioned iron phosphate crystals, so it has the advantages of high specific capacity and good rate performance. In other embodiments, other preparation methods or other lithium sources and carbon sources can be selected as raw materials according to actual needs, which are not limited here.

[0063] In a fifth aspect, an embodiment of the present application provides a positive electrode plate, comprising the lithium iron manganese phosphate positive electrode material provided in the fourth aspect of the present application.

[0064] The positive electrode plate of the present application includes the aforementioned lithium iron manganese phosphate positive electrode material, and thus has the advantages of high specific capacity and good rate performance.

[0065] In a sixth aspect, an embodiment of the present application provides a secondary battery, comprising the positive electrode plate provided in the fifth aspect of the present application.

[0066] The secondary battery of the present application includes the aforementioned positive electrode plate, and thus has the advantages of high specific capacity and good rate performance.

[0067] Some specific examples are listed below. It should be noted that the examples described below are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application. If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in the field or the product instructions shall be followed. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially. Among them, the composition analysis of the wet-process phosphoric acid and phosphate slurry used in the following examples and comparative examples is shown in Table 1: Table 1 Composition analysis of wet-process phosphoric acid and phosphate slurry

[0068] 1. Preparation method Example 1 The specific steps of preparing industrial-grade monoammonium phosphate crystals in this embodiment are as follows: (1) Wet-process phosphoric acid is mixed with phosphate slurry and subjected to desulfurization reaction. Ca in the phosphate slurry 2+ SO in wet-process phosphoric acid 4 2- The molar ratio is 1:1, the desulfurization reaction temperature is 80°C, the desulfurization reaction time is 4 h, and then pressure filtration is performed to obtain a first filter cake and a first filtrate. The first filter cake is recycled to the extraction process section and wet-process phosphoric acid is prepared again.

[0069] (2) A defluorinating agent is added to the first filtrate to carry out a defluorinating reaction. The defluorinating agent is sodium bicarbonate. The cations in the defluorinating agent react with the F in the first filtrate. - The molar ratio of is 1.2:3, the defluorination reaction temperature is 60°C, the defluorination reaction time is 2 h, and then the second filter cake and the second filtrate are obtained by pressure filtration. The second filter cake is dried and recovered as a fluorosilicate by-product.

[0070] (3) Liquid ammonia was added to the second filtrate to adjust the pH to 4.5 and conduct a neutralization reaction. The neutralization reaction temperature was 80°C and the neutralization reaction time was 1.5 h. The third filter cake and the third filtrate were then obtained by filter pressing. The third filter cake was dried and recovered as a slow-release nitrogen and phosphorus fertilizer by-product.

[0071] (4) After the third filtrate is concentrated, it is cooled and crystallized from 90°C to room temperature of 25°C, with a cooling rate of 0.3°C / min, a stirring rate of 180 rpm, a crystallization time of 5 h, and a solid-liquid ratio of 60% after cooling; it is then filtered, and the liquid phase is refluxed into wet-process phosphoric acid and reacted with the phosphate slurry for desulfurization again. The solid phase is dried to obtain industrial-grade monoammonium phosphate crystals.

[0072] Example 2 The specific steps of preparing industrial-grade monoammonium phosphate crystals in this embodiment are as follows: (1) Wet-process phosphoric acid is mixed with phosphate slurry and subjected to desulfurization reaction. Ca in the phosphate slurry 2+SO in wet-process phosphoric acid 4 2- The molar ratio is 0.9:1, the desulfurization reaction temperature is 80°C, the desulfurization reaction time is 4 h, and then the first filter cake and the first filtrate are obtained by pressure filtration. The first filter cake is recycled to the extraction process section and wet-process phosphoric acid is prepared again.

[0073] (2) A defluorinating agent is added to the first filtrate to carry out a defluorinating reaction. The defluorinating agent is sodium carbonate. The cations in the defluorinating agent react with the F in the first filtrate. - The molar ratio of is 1.2:3, the defluorination reaction temperature is 60°C, the defluorination reaction time is 2 h, and then the second filter cake and the second filtrate are obtained by pressure filtration. The second filter cake is dried and recovered as a fluorosilicate by-product.

[0074] (3) Liquid ammonia was added to the second filtrate to adjust the pH to 4.5 and conduct a neutralization reaction. The neutralization reaction temperature was 80°C and the neutralization reaction time was 1.5 h. The third filter cake and the third filtrate were then obtained by filter pressing. The third filter cake was dried and recovered as a slow-release nitrogen and phosphorus fertilizer by-product.

[0075] (4) After the third filtrate is concentrated, it is cooled and crystallized from 90°C to room temperature of 25°C, with a cooling rate of 0.3°C / min, a stirring rate of 180 rpm, a crystallization time of 5 h, and a solid-liquid ratio of 60% after cooling; it is then filtered, and the liquid phase is refluxed into wet-process phosphoric acid and reacted with the phosphate slurry for desulfurization again. The solid phase is dried to obtain industrial-grade monoammonium phosphate crystals.

[0076] Example 3 The specific steps of preparing industrial-grade monoammonium phosphate crystals in this embodiment are as follows: (1) Wet-process phosphoric acid is mixed with phosphate slurry and subjected to desulfurization reaction. Ca in the phosphate slurry 2+ SO in wet-process phosphoric acid 4 2- The molar ratio is 0.8:1, the desulfurization reaction temperature is 80°C, the desulfurization reaction time is 4 h, and then pressure filtration is performed to obtain a first filter cake and a first filtrate. The first filter cake is recycled to the extraction process section and wet-process phosphoric acid is prepared again.

[0077] (2) A defluorinating agent is added to the first filtrate to carry out a defluorinating reaction. The defluorinating agent is sodium hydroxide. The cations in the defluorinating agent react with the F in the first filtrate. - The molar ratio of is 1.2:3, the defluorination reaction temperature is 60°C, the defluorination reaction time is 2 h, and then the second filter cake and the second filtrate are obtained by pressure filtration. The second filter cake is dried and recovered as a fluorosilicate by-product.

[0078] (3) Liquid ammonia was added to the second filtrate to adjust the pH to 4.5 and conduct a neutralization reaction. The neutralization reaction temperature was 80°C and the neutralization reaction time was 1.5 h. The third filter cake and the third filtrate were then obtained by filter pressing. The third filter cake was dried and recovered as a slow-release nitrogen and phosphorus fertilizer by-product.

[0079] (4) After the third filtrate is concentrated, it is cooled and crystallized from 90°C to room temperature of 25°C, with a cooling rate of 0.3°C / min, a stirring rate of 180 rpm, a crystallization time of 5 h, and a solid-liquid ratio of 60% after cooling; it is then filtered, and the liquid phase is refluxed into wet-process phosphoric acid and reacted with the phosphate slurry for desulfurization again. The solid phase is dried to obtain industrial-grade monoammonium phosphate crystals.

[0080] Example 4 Compared with Example 3, the only difference is that in step (1), the desulfurization reaction temperature is 85°C.

[0081] Example 5 Compared with Example 3, the only difference is that in step (1), the desulfurization reaction temperature is 90°C.

[0082] Example 6 Compared with Example 3, the only difference is that in step (1), the desulfurization reaction time is 3 h.

[0083] Example 7 Compared with Example 3, the only difference is that in step (1), the desulfurization reaction time is 3.5 h.

[0084] Example 8 Compared with Example 3, the only difference is that in step (2), the cations in the defluorinating agent and the F in the first filtrate - The molar ratio is 1.4:3.

[0085] Example 9 Compared with Example 3, the only difference is that in step (2), the cations in the defluorinating agent and the F in the first filtrate - The molar ratio is 1.3:3.

[0086] Example 10 Compared with Example 3, the only difference is that in step (2), the defluorination reaction temperature is 65°C.

[0087] Embodiment 11 Compared with Example 3, the only difference is that in step (2), the defluorination reaction temperature is 70°C.

[0088] Example 12 Compared with Example 3, the only difference is that in step (2), the defluorination reaction time is 3 h.

[0089] Embodiment 13 Compared with Example 3, the only difference is that in step (2), the defluorination reaction time is 2.5 h.

[0090] Embodiment 14 Compared with Example 3, the only difference is that in step (3), liquid ammonia is added to the second filtrate to adjust the pH to 4.0 and perform a neutralization reaction.

[0091] Embodiment 15 Compared with Example 3, the only difference is that in step (3), liquid ammonia is added to the second filtrate to adjust the pH to 5.0 and perform a neutralization reaction.

[0092] Example 16 Compared with Example 3, the only difference is that in step (3), the neutralization reaction time is 1 h.

[0093] Embodiment 17 Compared with Example 3, the only difference is that in step (3), the neutralization reaction time is 2 h.

[0094] Embodiment 18 Compared with Example 3, the only difference is that in step (3), the neutralization reaction temperature is 70°C.

[0095] Embodiment 19 Compared with Example 3, the only difference is that in step (3), the neutralization reaction temperature is 90°C.

[0096] Embodiment 20 Compared with Example 3, the only difference is that in step (4), the cooling rate is 0.2 °C / min.

[0097] Embodiment 21 Compared with Example 3, the only difference is that in step (4), the cooling rate is 0.4 °C / min.

[0098] Embodiment 22 Compared with Example 3, the only difference is that in step (4), the stirring rate is 150 rpm.

[0099] Embodiment 23 Compared with Example 3, the only difference is that in step (4), the stirring rate is 200 rpm.

[0100] Embodiment 24 Compared with Example 3, the only difference is that in step (4), the crystallization time is 3 h.

[0101] Embodiment 25 Compared with Example 3, the only difference is that in step (4), the crystallization time is 4 h.

[0102] Embodiment 26 Compared with Example 3, the only difference is that in step (4), the solid-liquid ratio after cooling is 50%.

[0103] Embodiment 27 Compared with Example 3, the only difference is that in step (4), the solid-liquid ratio after cooling is 70%.

[0104] Comparative Example 1 Compared with Example 3, the only difference is that in step (1), the Ca in the phosphate slurry 2+ SO in wet-process phosphoric acid 4 2- The molar ratio is 0.7:1.

[0105] Comparative Example 2 Compared with Example 3, the only difference is that in step (1), the Ca in the phosphate slurry 2+ SO in wet-process phosphoric acid 4 2- The molar ratio is 1.1:1.

[0106] Comparative Example 3 Compared with Example 3, the only difference is that in step (1), the desulfurization reaction temperature is 70°C.

[0107] Comparative Example 4 Compared with Example 3, the only difference is that in step (1), the desulfurization reaction temperature is 100°C.

[0108] Comparative Example 5 Compared with Example 3, the only difference is that in step (1), the desulfurization reaction time is 2 h.

[0109] Comparative Example 6 Compared with Example 3, the only difference is that in step (1), the desulfurization reaction time is 5 h.

[0110] Comparative Example 7 Compared with Example 3, the only difference is that in step (2), the cations in the defluorinating agent and the F in the first filtrate - The molar ratio is 1.0:3.

[0111] Comparative Example 8 Compared with Example 3, the only difference is that in step (2), the cations in the defluorinating agent and the F in the first filtrate - The molar ratio is 1.5:3.

[0112] Comparative Example 9 Compared with Example 3, the only difference is that in step (2), the defluorination reaction temperature is 50°C.

[0113] Comparative Example 10 Compared with Example 3, the only difference is that in step (2), the defluorination reaction temperature is 80°C.

[0114] Comparative Example 11 Compared with Example 3, the only difference is that in step (2), the defluorination reaction time is 1.5 h.

[0115] Comparative Example 12 Compared with Example 3, the only difference is that in step (2), the defluorination reaction time is 1 h.

[0116] Comparative Example 13 Compared with Example 3, the only difference is that in step (3), liquid ammonia is added to the second filtrate to adjust the pH to 6.0 and perform a neutralization reaction.

[0117] Comparative Example 14 Compared with Example 3, the only difference is that in step (3), liquid ammonia is added to the second filtrate to adjust the pH to 3.5 and perform a neutralization reaction.

[0118] Comparative Example 15 Compared with Example 3, the only difference is that in step (3), the neutralization reaction time is 3 h.

[0119] Comparative Example 16 Compared with Example 3, the only difference is that in step (3), the neutralization reaction time is 0.5 h.

[0120] Comparative Example 17 Compared with Example 3, the only difference is that in step (3), the neutralization reaction temperature is 60°C.

[0121] Comparative Example 18 Compared with Example 3, the only difference is that in step (3), the neutralization reaction temperature is 100°C.

[0122] Comparative Example 19 Compared with Example 3, the only difference is that in step (4), the cooling rate is 0.5 °C / min.

[0123] Comparative Example 20 Compared with Example 3, the only difference is that in step (4), the cooling rate is 0.8 °C / min.

[0124] Comparative Example 21 Compared with Example 3, the only difference is that in step (4), the stirring rate is 250 rpm.

[0125] Comparative Example 22 Compared with Example 3, the only difference is that in step (4), the stirring rate is 300 rpm.

[0126] Comparative Example 23 Compared with Example 3, the only difference is that in step (4), the crystallization time is 7 h.

[0127] Comparative Example 24 Compared with Example 3, the only difference is that in step (4), the crystallization time is 8 h.

[0128] Comparative Example 25 Compared with Example 3, the only difference is that in step (4), the solid-liquid ratio after cooling is 30%.

[0129] Comparative Example 26 Compared with Example 3, the only difference is that in step (4), the solid-liquid ratio after cooling is 80%.

[0130] Comparative Example 27 Compared with Example 3, the only difference is that the desulfurization reaction process is not performed.

[0131] Comparative Example 28 Compared with Example 3, the only difference is that the defluorination reaction process is not performed.

[0132] Comparative Example 29 Compared with Example 3, the only difference is that the desulfurization reaction process and the defluorination reaction process are not carried out.

[0133] 2. Test Method 1. SEM test The MAP crystals prepared in Examples 1 to 5 were subjected to SEM testing using a MERLIN Compact field emission scanning electron microscope (model: Quanta200FEG) produced by Zeiss. The test results are shown in Figure 2 .

[0134] 2. Phosphorus pentoxide test The general method for determining phosphorus pentoxide content in inorganic chemical products, namely, the quinomolybdate gravimetric method, was used to determine the phosphorus pentoxide content in the solution to be tested. 2 O 5 The principle of this method is that in an acidic medium, phosphorus pentoxide in the test solution reacts with the added precipitant quinoline molybdate to form a precipitate, which is then filtered, dried, and weighed to calculate the P 2 O 5 content.

[0135] Test reagents: hydrochloric acid or nitric acid, quinoline molybdate solution.

[0136] Test equipment: glass sand crucible (filter plate pore size is 5 pm~15 pm), electric constant temperature drying oven (temperature controlled at 180 ℃±5℃ or 250 ℃±10℃).

[0137] Test steps: 1) Preparation of test solution: Weigh an appropriate amount of sample (containing about 600 mg of phosphorus pentoxide), place in a 100 mL beaker, add 20 mL of water and 5 mL of hydrochloric acid or nitric acid, cover with a watch glass, and boil for 10 min. After cooling, transfer to a 500 mL volumetric flask, add 10 mL of hydrochloric acid or nitric acid, dilute to the mark with water, and shake well.

[0138] 2) Preparation of blank test solution: Except for not adding sample, the amount of other reagents added is exactly the same as that of the test solution, and they are processed in the same way as the sample.

[0139] 3) Determination and calculation: Use a pipette to transfer 10 mL of the test solution and blank test solution to a 250 mL beaker, and add water to a total volume of about 100 mL. Cover with a watch glass, heat in a water bath until the temperature of the contents reaches 75℃±5℃, maintain for 30 seconds, and add 35 mL of quinoline molybdate solution. Cool to room temperature, and stir 3 to 4 times during the cooling process. Use a glass crucible that has been dried to a constant mass at 180℃±5℃ or 250℃±10℃ to filter the supernatant liquid, and wash the precipitate 5 to 6 times by decantation, using about 20 mL of water each time. Transfer the precipitate to a glass crucible and continue to wash with water 3 to 4 times. Place the glass crucible in an electric constant temperature drying oven at 180℃±5℃ for 45 minutes or at 250℃±10℃ for 15 minutes, take it out, place it in a desiccator to cool to room temperature, weigh it, and calculate and count the mass percentage of phosphorus pentoxide.

[0140] 3. Fluoride ion test The sample to be tested is decomposed with hydrochloric acid, and the pH of the solution is controlled to maintain 5.5-6.0 with citric acid-sodium citrate buffer solution, while eliminating the interference of aluminum, iron and other ions. A potentiometer is used, with a saturated calomel electrode as the reference electrode and a fluoride ion selective electrode as the indicator electrode, to measure the electrode potential, and the fluoride content is calculated using the working curve method.

[0141] Test reagents: hydrochloric acid, nitric acid, sodium hydroxide (200 g / L), citric acid-sodium citrate buffer solution (weigh 24 g citric acid, 270 g trisodium citrate, dissolve in water, and dilute to 1000 mL, mix well, pH 5.5-6.0), fluorine standard solution (1.0 mg / mL), bromocresol green indicator solution (1 g / L).

[0142] Test equipment: fluoride ion selective electrode, saturated calomel electrode, potentiometer, magnetic stirrer.

[0143] Test steps: 1) The sample is passed through a 125 μm test sieve, dried at 105-110°C for more than 2 h, and placed in a desiccator to cool to room temperature.

[0144] 2) Weigh 0.1-0.2 g of the sample, accurate to 0.0001 g, place in a 50 mL beaker, moisten with a small amount of water, add 10 mL of hydrochloric acid solution, stir for a while, let stand for 30 min, and stir every 10 min. Transfer to a 100 mL volumetric flask, dilute to the mark with water, and shake well. Let stand to clarify or dry filter, and take 10.0 mL of the clear solution and place in a 50 mL volumetric flask.

[0145] 3) Add five drops of citric acid-sodium citrate buffer solution and two drops of bromocresol green indicator solution, neutralize with sodium hydroxide solution until the solution turns blue, and then adjust the solution to yellow with nitric acid solution. Add 20 mL of citric acid-sodium citrate buffer solution, dilute to the mark with water, shake well, and pour into a dry 50 mL beaker.

[0146] 4) Insert a fluoride ion selective electrode and a saturated calomel electrode, measure the potential value at equilibrium under constant stirring with a magnetic stirrer, and find the corresponding fluoride amount on the working curve.

[0147] 5) Take 1.0, 2.0, 3.0, 5.0, 10.0 mL of fluorine standard solution and place them in a set of 50 mL volumetric flasks respectively, and add 1.0 mL of hydrochloric acid solution. Measure the potential value at equilibrium according to 7.2-7.3. Draw a working curve on semi-logarithmic coordinate paper with the potential value (mV) as the ordinate and the corresponding fluorine amount (mg) as the abscissa, and calculate the corresponding fluoride ion content. The data unit ppm recorded in the following examples and comparative examples can be converted to mg / kg.

[0148] 4. Crystal product component testing The components of the monoammonium phosphate (MAP) crystals prepared in Examples 1 to 3 and Comparative Examples 27 to 29 were tested using an inductively coupled plasma spectrometer (ICP). The test results are shown in Table 6.

[0149] III. Analysis of test results of various embodiments and comparative examples I. Test and analyze the influence of the desulfurization process conditions of the present application on the desulfurization effect and phosphorus yield. 2+ SO in wet-process phosphoric acid 4 2- The molar ratio, desulfurization reaction temperature and desulfurization reaction time were adjusted, and the SO 4 2- The remaining mass fraction (ppm) and P2 O 5 Yield (%), where P 2 O 5 The yield indicates the P in the first filtrate. 2 O 5 Quality and P in wet-process phosphoric acid 2 O 5 The mass ratio is due to the introduction of phosphate slurry for desulfurization during the desulfurization reaction, and the phosphate slurry also contains a certain amount of P 2 O 5 , so that the calculated P 2 O 5 The yield may be greater than 100%, as shown in Table 2.

[0150] Table 2 Statistical table of desulfurization process parameters and characterization parameters of Examples 1 to 7 and Comparative Examples 1 to 6

[0151] It can be seen from Table 2 that: a) For Ca in phosphate slurry 2+ SO in wet-process phosphoric acid 4 2- The molar ratio of Ca 2+ Relative to SO 4 2- The proportion gradually increases. Although the desulfurization effect is improved, the first filtrate P 2 O 5 The yield gradually decreased, proving that adding too much phosphate slurry will affect the phosphorus yield. 2+ SO in wet-process phosphoric acid 4 2- The molar ratio of is controlled within an appropriate range to obtain better desulfurization effect and phosphorus yield.

[0152] b) As for the desulfurization reaction temperature, it can be seen from the combination of Examples 3 to 5 and Comparative Examples 3 to 4 that as the desulfurization reaction temperature increases, the desulfurization effect first increases and then decreases. When the temperature is too low, the desulfurization effect is poor. When the temperature exceeds 90°C, side reactions will occur and the desulfurization effect will gradually decrease. It is more appropriate to control the desulfurization reaction temperature at 80 to 90°C.

[0153] c) As for the desulfurization reaction time, it can be seen from the combination of Examples 3, 6-7 and Comparative Examples 5-6 that when the desulfurization time is too short, the desulfurization effect is significantly poor, and when the time exceeds 4 hours, the desulfurization effect is slightly improved. Therefore, it is more appropriate to control the desulfurization reaction time to 3-4 hours.

[0154] II. Testing and analyzing the effects of the defluorination process conditions of the present application on the defluorination effect and phosphorus yield. Specifically referring to Examples 8 to 13 and Comparative Examples 7 to 12, the cations in the defluorination agent and the F in the second filtrate in the defluorination process were compared. - The molar ratio, defluorination reaction temperature and defluorination reaction time were adjusted, and the F content in the second filtrate was tested. - The remaining mass fraction (ppm) and P 2 O 5 Yield (%), where P 2 O 5 The yield indicates the P in the second filtrate. 2 O 5 Quality and P in wet-process phosphoric acid 2 O 5 The specific mass ratio is shown in Table 2.

[0155] Table 3 Statistical table of defluorination process parameters and characterization parameters of Examples 8 to 13 and Comparative Examples 7 to 12

[0156] It can be seen from Table 3 that: a) For the cations in the defluorinating agent and the F in the second filtrate - The molar ratio of 1.4:3 and 1.5:1 was used for the defluorination effect. The results of the above tests show that when the amount of defluorination agent added is too small, the defluorination effect is obviously poor. As the amount of defluorination agent added is gradually increased, the fluoride ion content is gradually reduced, and the phosphorus yield is also gradually reduced. When the molar ratio exceeds 1.4:3, the defluorination effect is slightly improved, which proves that too much defluorination agent will reduce the phosphorus yield. At the same time, the average particle size of the MAP crystals prepared in Examples 3, 8-9 and Comparative Examples 7-8 is tested. After comparison, it is found that when the amount of defluorination agent added is too large, the average particle size of the MAP crystals prepared in the subsequent preparation is reduced to 300-400 μm, which shows that too little fluoride ions are difficult to promote the crystallization of MAP. The cations in the defluorination agent and the F in the second filtrate are mixed. - It is more appropriate to control the molar ratio between (1.2~1.4):3.

[0157] b) As for the defluorination reaction temperature, it can be seen from Examples 3, 10-11 and Comparative Examples 9-10 that when the defluorination reaction temperature is too low, the defluorination effect is poor, and when the defluorination reaction temperature exceeds 80°C, the defluorination effect is slightly improved. Therefore, it is more appropriate to control the defluorination reaction temperature at 50-80°C.

[0158] c) As for the defluorination reaction time, it can be seen from the combination of Examples 3, 12-13 and Comparative Examples 11-12 that when the defluorination reaction time is too short, the defluorination effect is obviously poor, so it is more appropriate to control the defluorination reaction time to 2-4 h.

[0159] III. Test and analyze the influence of the neutralization process conditions of the present application on the defluorination effect and phosphorus yield. Specifically refer to Examples 14 to 19 and Comparative Examples 13 to 18, adjust the pH value, neutralization reaction temperature, and neutralization reaction time in the neutralization process, and test the F in the third filtrate. - The residual mass fraction (ppm) and water-soluble phosphorus yield (%) of the third filtrate, where the water-soluble phosphorus yield represents the P 2 O 5 Quality and P in wet-process phosphoric acid 2 O 5 The specific mass ratio is shown in Table 4.

[0160] Table 4 Statistical table of neutralization process parameters and characterization parameters of Examples 14 to 19 and Comparative Examples 13 to 18

[0161] It can be seen from Table 4 that: a) Regarding the control of pH value during the neutralization reaction, it can be seen from Examples 3, 14-15 and Comparative Examples 13-14 that as the pH value increases, the F in the third filtrate - The residual mass fraction of phosphate decreased first and then increased, while the water-soluble phosphorus yield decreased. When the pH value was too high, a viscous precipitate would be formed, which made it difficult for monoammonium phosphate to form, thereby significantly reducing the water-soluble phosphorus yield. It was more appropriate to control the pH value at 4-5.

[0162] b) For the neutralization reaction time, it can be seen from the combination of Examples 3, 16-17 and Comparative Examples 15-16 that when the neutralization reaction time is too short, the F in the third filtrate - If the residual mass fraction is too high, it is more appropriate to control the neutralization reaction time to 1.5~3 h.

[0163] c) As for the neutralization reaction temperature, it can be seen from Examples 3, 18-19 and Comparative Examples 17-18 that when the neutralization reaction temperature is too high, the water-soluble phosphorus yield is significantly reduced. The reason is that the solubility of monoammonium phosphate increases sharply with increasing temperature, and as the temperature is too high, the amount of ammonia escape increases, affecting the stability of the generated monoammonium phosphate. Therefore, it is more appropriate to control the neutralization reaction temperature at 70-90°C.

[0164] IV. Testing and analyzing the effects of the cooling crystallization process conditions of the present application on the MAP crystal yield and the average crystal particle size, referring specifically to Examples 20 to 27 and Comparative Examples 19 to 26, adjusting the cooling rate, stirring rate, crystallization time, and solid-liquid ratio after cooling in the cooling crystallization process, and testing the MAP crystal yield (%) and average particle size (μm), wherein the water-soluble phosphorus yield represents the P in the third filtrate. 2 O 5 Quality and P in wet-process phosphoric acid 2O 5 The specific mass ratio is shown in Table 5.

[0165] Table 5 Statistical table of cooling crystallization process parameters and characterization parameters of Examples 20 to 27 and Comparative Examples 19 to 26

[0166] Combination Figure 2 From Table 5 we can see that: a) Figure 2 The MAP crystals prepared in Examples 1 to 5 have a significant prism-like structure, with four-sided pyramids at both ends of the prism, appropriate particle size, and uniform morphology.

[0167] b) As for the cooling rate during the cooling crystallization process, it can be seen from Examples 3, 20-21 and Comparative Examples 19-20 that the adjustment of the cooling rate has no significant effect on the MAP crystal yield, while when the cooling rate is too fast, the crystal particle size is small, and when the cooling rate is too slow, the crystal particle size is large and the morphology is quite different. By controlling the cooling rate to 0.2-0.6°C / min, high-quality MAP crystals with suitable particle size and uniform morphology can be obtained.

[0168] c) For the stirring rate during the cooling crystallization process, combined with Examples 3, 22-23 and Comparative Examples 21-22, it can be seen that the stirring rate adjustment has no significant effect on the MAP crystal yield. When the stirring speed is too slow, the solid phase mass transfer rate and the solute growth rate are low, and the crystal particle size is small; when the rotation speed reaches 180rpm, the solid phase mass transfer rate and the solute growth rate increase rapidly, and the average particle size of the crystal increases rapidly; when the stirring speed is too fast, the impact strength between the crystal and the stirring paddle will further increase; at this time, the secondary nucleation phenomenon between crystals and the probability of crystal breakage, and the violent collision between the crystal and the stirring paddle will also greatly increase, ultimately resulting in a decrease in the average particle size of the product. Therefore, as the stirring speed gradually increases, the average particle size of the crystal tends to increase first and then decrease, so it is more appropriate to control the stirring rate to 150-300 rpm.

[0169] d) As for the crystallization time during the cooling crystallization process, it can be seen from the combination of Examples 3, 24-25 and Comparative Examples 23-24 that the adjustment of the crystallization time has no significant effect on the MAP crystal yield, while when the crystallization time is too short, the crystal particle size is small, and when the crystallization time is too long, the crystal particle size is large and the morphology difference is large. It is more appropriate to control the crystallization time to 4-7 h.

[0170] e) As for the solid-liquid ratio after cooling in the cooling crystallization process, it can be seen from Examples 3, 26-27 and Comparative Examples 25-26 that the adjustment of the solid-liquid ratio after cooling has a significant effect on the MAP crystal yield. Although increasing the solid-liquid ratio after cooling is beneficial to improving the MAP crystal yield, too high a solid-liquid ratio will lead to a slower crystal growth rate, a significantly increased crystal particle size and obvious morphology differences, making it difficult to obtain high-quality MAP crystals with uniform morphology and suitable particle size. It is more appropriate to control the solid-liquid ratio after cooling to 30-60%.

[0171] V. Testing and analyzing the effect of the desulfurization reaction process and the defluorination reaction process described in the present application on the quality of the prepared MAP crystals. Specifically referring to Examples 1 to 3 and Comparative Examples 27 to 29, the components of the finally prepared MAP crystals were tested, as shown in Table 6.

[0172] Table 6

[0173] It can be seen from Table 6 that the average particle size of MAP crystals is mainly affected by sulfate ions. Too high sulfate ion concentration will lead to a significant increase in particle size. The principle is that SO 4 2- With PO 4 3- Similar and with strong hydrogen bonding ability, SO 4 2- It may enter the cylindrical and conical surfaces of MAP, thereby affecting the growth rate of the solution and causing the crystal particle size to increase. Therefore, the aforementioned desulfurization reaction process of the present application is crucial to obtaining high-quality MAP crystals with uniform morphology and appropriate particle size.

[0174] When the desulfurization reaction process or the defluorination reaction process is not performed, the sulfur and fluorine impurities in the obtained MAP crystals are significantly increased, while Examples 1 to 3 using the desulfurization reaction process and the defluorination reaction process of the present application can significantly reduce the sulfur and fluorine impurities and improve the quality of the MAP crystals.

[0175] In summary, the present application prepares the precursor by the co-precipitation method, so that the precursor has a regular and uniform morphology, and the LMFP positive electrode material prepared from the precursor has good electrochemical properties.

[0176] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. An industrial grade monoammonium phosphate crystal, characterized in that: The industrial-grade monoammonium phosphate crystal has a prismatic structure, with four-sided pyramids at both ends of the prism, a particle size of 500-700 μm, and an aspect ratio of (2-4):1; In terms of mass percentage, the industrial-grade monoammonium phosphate crystals have a P2O5 content greater than 61%, a N content greater than 11.5%, and a F ion content of 50-150 mg / kg.

2. A method for preparing industrial-grade monoammonium phosphate crystals as claimed in claim 1, characterized in that: The following steps are involved: Mixing wet-process phosphoric acid with phosphate slurry and performing a desulfurization reaction, followed by solid-liquid separation to obtain a first filter cake and a first filtrate; A defluorinating agent is added to the first filtrate to perform a defluorinating reaction, followed by solid-liquid separation to obtain a second filter cake and a second filtrate; An ammonia solution is added to the second filtrate to adjust the pH to 4-5 and perform a neutralization reaction, followed by solid-liquid separation to obtain a third filter cake and a third filtrate; The third filtrate is concentrated, cooled and crystallized, and solid-liquid separated to obtain industrial-grade monoammonium phosphate crystals.

3. The method for preparing industrial-grade monoammonium phosphate crystals according to claim 2, characterized in that: In the step of mixing wet-process phosphoric acid with phosphate slurry and performing a desulfurization reaction, the desulfurization reaction temperature is 80-90° C. and the desulfurization reaction time is 3-4 hours; The mass percentage of P2O5 in the wet-process phosphoric acid is greater than 20%, and the Ca 2+ SO4 in the wet process phosphoric acid 2- The molar ratio is (0.8~1.0):

1.

4. The method for preparing industrial-grade monoammonium phosphate crystals according to claim 2, characterized in that: In the step of adding a defluorinating agent to the first filtrate for defluorination reaction, the defluorination reaction temperature is 50-80° C. and the defluorination reaction time is 2-4 h; and / or The defluorinating agent comprises at least one of sodium hydroxide, sodium carbonate, sodium bicarbonate, potassium hydroxide, potassium carbonate and potassium bicarbonate, and the cations in the defluorinating agent are compatible with the F in the first filtrate. - The molar ratio is (1.2~1.4):

3.

5. The method for preparing industrial-grade monoammonium phosphate crystals according to claim 2, characterized in that: In the neutralization step, the neutralization temperature is 70-90° C. and the neutralization time is 1.5-3 h; and / or The ammonia-containing solution includes at least one of liquid ammonia and aqueous ammonia; The specific conditions of the cooling crystallization include: a cooling rate of 0.2-0.6°C / min, a stirring rate of 150-300 rpm, a crystallization time of 4-7 h, and a solid-liquid ratio of 30-60% after cooling.

6. The method for preparing industrial-grade monoammonium phosphate crystals according to claim 2, characterized in that: After the cooling crystallization and solid-liquid separation, the obtained solid phase is the industrial-grade monoammonium phosphate crystal, and the liquid phase is refluxed into the wet-process phosphoric acid and undergoes a desulfurization reaction again with the phosphate slurry; The first filter cake is recycled to the extraction process section in the wet-process phosphoric acid preparation process to prepare the wet-process phosphoric acid; The second filter cake is dried and recycled as a fluorosilicate product; The third filter cake is dried and recycled as a slow-release nitrogen and phosphorus fertilizer.

7. An iron phosphate crystal, characterized in that: The iron phosphate crystals are prepared by a mixed reaction of an iron salt solution, an oxidant and the industrial-grade monoammonium phosphate crystals according to claim 1; Wherein, the iron salt in the iron salt solution includes at least one of ferrous sulfate, ferrous chloride, ferric sulfate and ferric chloride, and the oxidant includes hydrogen peroxide.

8. A lithium iron phosphate positive electrode material, characterized in that: The lithium iron phosphate positive electrode material is prepared by a mixed reaction of the iron phosphate crystals described in claim 7 and a lithium source.

9. A positive electrode sheet, characterized in that: Including the lithium iron manganese phosphate positive electrode material as described in claim 8.

10. A secondary battery, characterized in that: Including the positive electrode sheet as described in claim 9.

Citation Information

Patent Citations

  • Method for producing monoammonium phosphate and magnesium ammonium phosphate by using wet concentrated phosphoric acid residues

    CN104058378A

  • Method for directly producing battery-grade monoammonium phosphate from wet-process phosphoric acid

    CN115285956A

  • Method for preparing battery-grade lithium manganese phosphate composite material by utilizing minerals and application of battery-grade lithium manganese phosphate composite material

    CN115448284A

  • Preparation method of high-quality industrial-grade monoammonium phosphate

    CN116425132A

  • Method and device for improving phosphorus yield in monoammonium phosphate prepared from wet-process phosphoric acid

    CN117945372A

Cited By

  • Preparation method of manganese hydrogen phosphate precursor and manganese hydrogen phosphate precursor

    CN121134714A